Green Sukuk the Perspective of Sharia Economic Law: A Development Financing Instrument for Achieving the SDGs - Hubbul Wathan; Anriza Witi Nasution; Sulfi Amri Bin Sulaiman (Profetika: Jurnal Studi Islam, 2025)
Objective: This study aims to analyze the role of Green Sukuk as a sustainable development financing instrument from the perspective of Islamic economic law, while also examining its contribution to achieving the Sustainable Development Goals (SDGs). Theoretical framework: This study is grounded in the principles of Islamic jurisprudence (fiqh muamalah), maqashid al-shari'ah, and sustainable finance theory, which emphasize justice, sustainability, and social responsibility. Literature review: the literature review highlights the concept and evolution of green sukuk, the theoretical framework of sharia: maqashid, maslahah, and risk-sharing, standards and governance: sharia-ESG. Methods: The research method used is qualitative with a juridical normative approach, through the analysis of regulatory documents, fatwas, and reports on the issuance of Green Sukuk. The results: The results show that Green Sukuk not only fulfills sharia principles but is also effective in supporting environmentally friendly projects, such as renewable energy, water management, and green transportation. Implications: These findings imply that Green Sukuk can be a strategic instrument for both the government and the private sector in integrating sharia values ​​with the global sustainable development agenda. Novelty: The novelty of this research lies in the integrative approach that connects sharia economic law with green financial instruments, while also positioning Green Sukuk as an innovative financing model that is in line with maqashid al-syariah and SDGs.